Strategi Pengembangan Atraksi Seni Calung Berbasis Kearifan Lokal di Ranca Indah - Desmonda Aresta; Rachel Natasya; Violen Helianolita; Derick Tayindra; Budi Setiawan (Sadar Wisata: Jurnal Pariwisata, 2026)
This research is motivated by the importance of developing cultural attractions as part of a strategy to strengthen the appeal of community-based tourism destinations while also preserving local wisdom in the midst of modern tourism development. One cultural potential that can be developed is calung music, a traditional Sundanese bamboo musical instrument that contains aesthetic, educational, and cultural identity values of the local community. This study aims to analyze the development strategy of calung musical art attractions as a local wisdom–based tourism attraction in the Thematic Tourism Village of Ranca Indah, Serpong, South Tangerang. The research method used is a qualitative approach with data collection techniques including in-depth interviews with the head of the tourism awareness group (Pokdarwis), field observations, and literature studies related to culture-based tourism development. Data analysis was conducted using triangulation techniques to improve the validity and accuracy of the research findings. The results show that the development of calung musical attractions is carried out through several strategies, including preparation and observation of performance locations, organizing calung training workshops for the community as an effort to preserve cultural heritage, developing calung games as educational tourism activities for visitors, and organizing cultural performances that combine calung music and jaipong dance as the main attraction. These activities not only strengthen local cultural identity but also increase community participation in managing the tourism village. The impact of this development includes the creation of authentic tourism experiences, increased potential of local cultural attractions, and opportunities for developing culture-based tourism packages in the Ranca Indah Thematic Tourism Village.